Pharmacokinetic Modification of Controlled Release Matrix Tablets of Balsalazide - Palanisamy Vishnu (Journal of Global Pharma Technology, 2019)
Balsalazide is used to treat a certain bowel disease (ulcerative colitis) and it also helps to reduce symptoms of ulcerative colitis such as diarrheal, rectal bleeding and stomach pain.  It has a short half life and under goes extensive first pass metabolism. In the present study, balsalazide  600mg controlled release matrices were prepared by wet granulation method and in vitro drug dissolution studies were performed to find out the drug release rate and patterns. Eudragit L-100, Eudragit RSpo, lactose and their combination were used as rate controlling polymer. Tablets were formulated using different polymers ratios. As In vitro drug releaser was carried out using USP type II (paddle method ) at 50 rpm in 900ml of acetic dissolution medium(pH 1.2) for 2 hrs, followed by 900ml alkaline dissolution medium (Ph7.4) upto 12 hrs. Mean dissolution time is used to characterize drug release rate from a dosage form and indicates the drug retarding efficiency of polymer. When Eudragit L 100 and Eudragit RSpo were used alone as the only retarding polymer, a sustained drug release pattern were not absorbed while, combination in the matrix almost doubled the time required for releasing the drug. Several kinetic models were applied to the dissolution profiles to determine the drug release kinetics.